Conference in Ohio aims to highlight Malaysias profile on world stage - Borneo Post, (Kuching) (Borneo Post (Kuching), 2017)
SIBU: The University of Ohio s Tun Abdul Razak Chair, in collaboration with the university's Office of Global Affairs and International Studies and its Department of Political Science, will be hosting an international conference 'Malaysia and the World: CrossRegional Perspectives on Race, Religion and Ethnic Identity' from March 24 to 26 at Athens, Ohio, in the US.